2011
DOI: 10.1254/jphs.10r34fm
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Ameliorative Actions of Polyunsaturated Fatty Acids Against Neuronal Diseases: Implication of Fatty Acid–Binding Proteins (FABP) and G Protein–Coupled Receptor 40 (GPR40) in Adult Neurogenesis

Abstract: Abstract. Adult neurogenesis in the mammalian brain is well-known to occur in the subgranular zone of the hippocampus. As the hippocampus is related to learning, memory, and emotions, adult hippocampal neurogenesis possibly contributes to these functions. Adult neurogenesis is modulated by polyunsaturated fatty acids (PUFA) such as docosahexaenoic and arachidonic acids that are essential for normal brain development, maintenance, and function. They are reported to improve spatial learning and memory in rodents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 129 publications
0
15
1
Order By: Relevance
“…Second, ω-3 fatty acids increase cell viability through neuroprotective and anti-apoptotic mechanisms [57], and they may reduce neuronal oxidative stress. Third, ω-3 fatty acids can promote neurogenesis and long term potential (LTP) formation in the hippocampus [58], and improve the function of the hippocampus. Calderon et al [59] also found that ω-3 fatty acids could promote the survival of hippocampal neurons, and increase the number and length of neuronal processes significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Second, ω-3 fatty acids increase cell viability through neuroprotective and anti-apoptotic mechanisms [57], and they may reduce neuronal oxidative stress. Third, ω-3 fatty acids can promote neurogenesis and long term potential (LTP) formation in the hippocampus [58], and improve the function of the hippocampus. Calderon et al [59] also found that ω-3 fatty acids could promote the survival of hippocampal neurons, and increase the number and length of neuronal processes significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of GPR40 and GPR120 to help mediate taste perception lead some researchers to ponder if these are valuable targets for fighting obesity [38]. It is even possible that these receptors are important in neurogenesis and neurodevelopment [39]. One preliminary line of evidence is that immunostaining of newborn neurons is especially high for GPR40 versus mature neurons [40].…”
Section: Gpcrs and Fatty Acidsmentioning
confidence: 99%
“…46,47 Along these lines, activation of GPR40 by thiazolidinediones 48 but, generally, not by long chain cis-FA, is cytotoxic 49 ; in fact, cytoprotective effects of cis-AA is described. 50,51 On the contrary, TAA have been consistently found to be toxic, [16][17][18]25 and we now found that their effects are mediated via GPR40 (Figures 2-4). This apparent discrepancy between effects of different FAs is most likely attributable to activation of distinct allosteric sites on the receptor by different molecular structures.…”
Section: Discussionmentioning
confidence: 49%